Study on phenolphthalein poly(ether sulfone)‐modified cyanate ester resin and epoxy resin blends. Issue 11 (12th August 2015) - Wang, Guan; Wang, Rongguo; Fu, Gang; Gao, Tangling; Fu, Chunming; Kuang, Hong; Yang, Fan; Jiao, Weicheng; Hao, Lifeng; Liu, Wenbo
<x xml:space="preserve">Abstract</x> In this work, the phenolphthalein poly(ether sulfone) (PES‐C)‐modified cyanate ester (CE) and epoxy (EP) blends were prepared. This work mainly discusses the curing behaviors, fracture toughness, dynamic mechanical properties, and thermal and mechanical properties of the blends. The Fourier transform infrared and differential scanning calorimetric analyses are used to confirm the curing behaviors, demonstrating that the main reaction pathways are not varied with the addition of PES‐C, but the reaction rate could be evidently accelerated. The fracture morphologies of the blends are observed by Scanning electron microscope (SEM) and the fracture causes of the failed surface are also analyzed. With the addition of PES‐C, the modified blends display higher fracture toughness (KIc) and impact strength when compared with neat CE. Domain sizes of the blends first increase then decrease with the addition of PES‐C. The results of dynamic mechanical analysis and thermogravimetric analysis show that the Tg, storage modulus, and thermal stability of the crosslink network slightly decreases with the addition of PES‐C. The mechanical strength of blends with the addition of PES‐C is far better than that of the blends without PES‐C both at ambient temperature and elevated temperature. POLYM. ENG. SCI., 55:2591–2602, 2015. © 2015 Society of Plastics Engineers